Saponins of Dipsacus Azureus Plant and Their Hypocholesterolemic Activity (Texas Journal of Multidisciplinary Studies, 2023)
The aerial part of the plant Dipsacus azureus was extracted with 80% ethanol. The extract was concentrated and precipitated with acetone (sum of saponins), and the remaining residue was fractionated into aqueous, n-butanol and chloroform parts. The acetone-precipitated precipitate (sum of saponins) and aqueous fractions were examined for hypocholesterolemic properties.